What is Architecture? - Martienssen, Rex D (Association of Transvaal Architects, the Natal Institute of Architects and the South African Institute of Quantity Surveyors, 1925)
For music being purely in time, and architecture being purely in space, each is convertable into the other, and that which in music is expressed by means of harmonious intervals of time and pitch, successfully may be translated into corresponding intervals of architectural void and solid, height and width.
Keywords: Architecture